Windfalls? Costs and benefits of investment tax incentives due to financial constraints - Orihara, Masanori; Suzuki, Takafumi (Journal of Corporate Finance, 2023)
We find that financially unconstrained firms claim temporary investment tax incentives more frequently than their constrained counterparts. Notably, these extensive claims from unconstrained firms do not lead to an incremental total investment beyond pre-claim levels; instead, these firms appear to treat the tax cut as a windfall, increasing their cash holdings in subsequent years. In contrast, constrained firms increase their investments relative to pre-claim levels when they manage to claim tax incentives. Our analysis draws from a 2014 tax reform in Japan which introduced both an investment tax credit and bonus depreciation, available for nearly three years. We use a proprietary tax return survey that provides data on tax incentive claims across both public and private firms. Our findings highlight a novel tradeoff of investment tax incentives: while stimulating investments among financially constrained firms upon claiming tax incentives, they also disproportionately allocate tax benefits to unconstrained firms, not necessarily resulting in the intended investment stimulation.